Interface Wave Sediment Profiler: A measurement system for shear wave speed - Potty, Gopu R.; Miller, James H.; Peters, Donald; Carroll, Megan M.; Baker, John; Butler, Alex (OCEANS 2016 MTS/IEEE Monterey, 2016)
Shear wave properties of ocean bottom sediments are of great importance for sonar system performance. The frequency dependence of attenuation in the sediment is a subject of intensive investigations by a number of researchers and institutions. One of the key components of the attenuation is the conversion of acoustic energy into shear waves at interfaces including the seafloor. In addition to its importance in acoustic propagation shear properties are also of significance in geotechnical applications. Many geotechnical parameters used to analyze the strength and stability of sediments are correlated to shear wave speed. The propagation speed and attenuation of the interface wave (Scholte wave) are closely related to shear-wave speed and attenuation over a depth of 1-2 wavelengths into the seabed. One method to estimate the shear wave speed as a function of depth in the sediment is to utilize this property. An inversion scheme to estimate the shear wave speed in the sediment as a function of depth based on this principle has been developed and validated. The Interface Wave Sediment Profiler (iWaSP) is a measurement system for the estimation of bottom properties such as shear speed and attenuation in the top 1-2 meters of a variety of sediment types (including sand, silt and mud) with a wideband, vibratory source and accelerometers with bandwidth up to 1 kHz. This measurement system is based on the inversion of shear wave properties using Scholte wave dispersion. It compliments an existing system consisting of a low frequency geophone receive array and data acquisition package. This existing geophone system is capable of measuring interface waves of frequencies below 50 Hz and estimating the sediment properties down to 10s of meters with a depth resolution of the order of a meter in the near seafloor sediment layer. This low frequency system has been successfully tested by deploying it in a few shallow water locations in Narragansett Bay. The new higher frequency system will complement the existing one since by using high frequency source and receivers to achieve higher resolution (10s of cm) in the near seafloor sediment layer (top 1-2 m). Both the existing and new system will be fully compatible and complementary. By deploying both the systems simultaneously we can infer shallow sediments with high resolution (using high frequencies) and deeper sediment layers (using low frequencies). The new system includes an electronic vibratory source capable of generating interface waves in the seafloor at frequencies up to 1 kHz and a short line array of accelerometers with matching frequency response. A deployment system to house the source and extend the receive array is also being developed. The iWaSP system is being designed to provide adequate coupling between the receiver and the sediment and decouple the source-induced structural vibration from the receive array. This system is proposed to be deployed in the New England Mud Patch location (south of Martha's Vineyard), in water depths of approximately 100 m, as part of the Seabed Characterization Experiment in 2017. [Work supported by Office of Naval Research under the DURIP program]